IoT Prototype Development of Automatic Fish Feeder and Water Replacement - Ratnasari, Devi; Rodhiyah; Pramudwiatmoko, Arif (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2020)
In raising the freshwater fish in the aquarium, we need to pay attention on the fish’s health by noticing the feeding time and the aquarium cleanness. The busy fish owners sometimes do not have time to clean the aquarium and replace the water. The food is even not given regularly. The system which can be developed to help the fish owners in handling the problems in raising the fish is the scheduled automatic feeding monitoring system and automatic water changer when the water has turned turbid. The system is developed by using the NodeMCU ESP8266 as the controlling center and in the same time it helps the system to connect to internet. The system is equipped with the website page to help the fish owner in monitoring the aquarium condition from the distance.